Peoples’ Participation in Rural Development: A Case Study in Dibrugarh District of Assam - Dutta, Biraj (Prabandhan: Indian Journal of Management, 2012)
Participation in general means that process wherein people are closely involved in economic, social, cultural and political affairs which affect their lives. When viewed from the dimension of dealing with development plans or programmes for the people, it simply implies participation of people in all stages viz- planning, formulation, decision making, sharing the benefit of development, monitoring and evaluation appraisal. Thus, the successful implementation of the various rural development programmes not only depends upon the effective functioning of the various administrative agencies viz- DRDA, Blocks and Village Level functionaries, but also depends upon the effective people’s participation in all the levels of people’s participation. For the present study, District Rural Development Agency, Dibrugarh, Assam has been selected while dealing with the problem of people’s participation in rural development programmes, and it is desirable to discuss the level of people’s participation in rural development activities implemented by the DRDA, Dibrugarh, Assam.